1994
DOI: 10.1128/jb.176.11.3278-3285.1994
|View full text |Cite
|
Sign up to set email alerts
|

Roles of LysP and CadC in mediating the lysine requirement for acid induction of the Escherichia coli cad operon

Abstract: Expression of the Escherichia col cadBA operon, Encoding functions required for the conversion of lysine to cadaverine and for cadaverine excretion, requires at least two extracellular signals: low pH and a high concentration of lysine. To better understand the nature of the lysine-dependent signal, mutants were isolated which expressed a cad4-lacZ transciription fusion in the absence of lysine while retaining pH regulation. The responsible mutation in one of these isolates (EP310) was in cadC, a gene encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 38 publications
2
122
0
Order By: Relevance
“…Together, these results suggest that our previous demonstration of low-pH induction of cadA transcription (25) occurs at the level of increased bicistronic cadBA and monocistronic cadA mRNA. pH-regulated induction of cadBA in E. coli is completely dependent on CadC in that a cadC null mutant does not express cadBA under any conditions tested (28). Unlike the case for E. coli, though, V. cholerae shows basal-level expression of cadBA transcript at neutral pH.…”
Section: Discussionmentioning
confidence: 85%
“…Together, these results suggest that our previous demonstration of low-pH induction of cadA transcription (25) occurs at the level of increased bicistronic cadBA and monocistronic cadA mRNA. pH-regulated induction of cadBA in E. coli is completely dependent on CadC in that a cadC null mutant does not express cadBA under any conditions tested (28). Unlike the case for E. coli, though, V. cholerae shows basal-level expression of cadBA transcript at neutral pH.…”
Section: Discussionmentioning
confidence: 85%
“…It can therefore be concluded that in all clusters, the permease and decarboxylase genes are present. Aminoacyl-tRNA synthetase was located in some clusters only (Neely et al, 1994;Lucas et al, 2003;Connil et al, 2002;Fernández et al, 2004).…”
Section: Comparative Analysis Of the Hdc Cluster Organizationmentioning
confidence: 99%
“…The cadA gene mapped at 93.7 min is co-transcribed with the preceding cadB gene that encodes a lysine/cadaverine antiporter. The cadA and cadB genes constitute an acidinducible operon under a dual control: a positive regulation by the product of cadC located immediately upstream of cadBA and a negative regulation by the product of cadR (= lysP) located at 46.5 min (Neely et al, 1994). The absence of any homologous sequence between the PcadBA and PldcC promoters suggests that ldcC is under a regulation different from that of cadBA.…”
mentioning
confidence: 99%